The Relationship Between State Funded Merit Scholarships and Student Loan Debt (Higher Education Politics and Economics, 2021)
This paper uses a sample of 13,643 students attending a 4-year state university in Florida to estimate a selection-bias corrected quantile regression of loan debt at graduation.  The study investigates whether the debt levels of students who received the Florida Bright Futures (FBF) scholarship are significantly different from the debt levels of students who did not receive the scholarship.  The empirical results show that FBF recipients accumulate higher debt, on average, than similar students who did not receive the award.  However, for students from the lowest income households and with the highest levels of debt, the FBF scholarship award does reduce the overall amount of debt they accumulate.